Sequência didática sobre ensino de óptica geométrica e a visão do olho humano - CARDOSO, Rogério dos Santos (2018)
The use of didactic sequences has been gaining more and more space in pedagogical making, since they allow students and teachers a simple and organized path in search of processes that result in meaningful learning. This work shows an application of a didactic sequence for teaching Geometric Optics and the vision of the human eye that was developed with Secondary School students. Throughout this sequence, emphasis was given to theoretical knowledge, experimental activities and research on the applications of themes in everyday situations, with a view to developing a critical view of students about the reality that surrounds them. Ausubel's meaningful learning theory, Vergnaud's conceptual field theory, Novak's learning research developed, and Moreira's critical learning theory are the theoretical foundations that underpin all this work. The evaluation of this activity was carried out throughout the whole process of implementation of the didactic sequence, giving attention to the search for different evaluation instruments in order to perceive evidence of the existence of significant critical learning in the students' responses. With the use of the different evaluation instruments, we can affirm that the didactic sequence was successful in its implementation, from the results presented in the summative evaluations, in the results obtained from the experimental activities, to the capacity of the students to behave reflexively and critically, in relation their own learning and the use of knowledge in their daily lives.